Next-Step Strategies for Panic Disorder Refractory to Initial Pharmacotherapy - Simon, NM (2009)
BACKGROUND: More data is needed to guide next step interventions for panic disorder refractory to initial intervention. METHOD: This 24-week randomized clinical trial (RCT) consisted of three phases. Phase 1 is a 6-week lead-in with open-label sertraline flexibly dosed to 100mg (or escitalopram equivalent) to prospectively define treatment refractoriness (lack of remission). Phase 2 is a six-week double blind RCT of (1) increased dose serotonin selective reuptake inhibitor (SSRI) versus (2) continued SSRI plus placebo. Phase 3 is a 12-week RCT of added cognitive-behavioral therapy (CBT) compared to “medication-optimization” (MO) with SSRI plus clonazepam. Primary endpoints were remission and change in Panic Disorder Severity Scale (PDSS) score in the intent to treat sample in each phase. RESULTS: In Phase 1, 20.5% (8/39) achieved remission, and only baseline severity predicted endpoint PDSS (β (SE)= 1.04(0.15), t=6.76, p<0.000). In Phase 2, increasing the SSRI dose did not result in greater improvement or remission rates (placebo 15% [n=2] vs. increased dose 9%[n=1]: FET p=n.s.). In Phase 3, remission was minimal (MO = 11%; CBT =10%), with a lack of group difference in PDSS reduction (t(df)=0.51(17), p>0.60) consistent with a small effect size (d=0.24). CONCLUSION: Although power was limited and larger studies are needed, we failed to find evidence for greater benefit of increased SSRI dose versus continuation of current dose for panic disorder symptomatic after 6 weeks at moderate dose. Further, augmentation with CBT or medication optimization with clonazepam augmentation in non-remitted panic after 12 weeks of an SSRI did not differ, suggesting both are reasonable next-step options. However, low overall remission rates in this comorbid refractory population suggest better predictors of response to specific treatments over time and additional interventions are needed.